Parotitis After Endoscopic Retrograde Cholangiopancreatography - Li, Feng (ACG Case Rep J, 2020)
End-stage liver disease management requiring orthotopic liver transplantation is being increasingly performed across the United States. However, some of the most common postoperative complications are bile leak and anastomotic stricture formation. These complications are successfully managed in most patients with endoscopic retrograde cholangiopancreatography (ERCP). We hereby report a case of acute parotitis, an extremely uncommon complication after ERCP. The exact etiology of this complication is not known. However, we discuss the treatment and purported mechanistic risk factors of this unusual post-ERCP adverse event.